2021
DOI: 10.1186/s12910-021-00641-3
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress and ethical climate in intensive care medicine during COVID-19: a nationwide study

Abstract: Background The COVID-19 pandemic has created ethical challenges for intensive care unit (ICU) professionals, potentially causing moral distress. This study explored the levels and causes of moral distress and the ethical climate in Dutch ICUs during COVID-19. Methods An extended version of the Measurement of Moral Distress for Healthcare Professionals (MMD-HP) and Ethical Decision Making Climate Questionnaire (EDMCQ) were online distributed among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
189
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(209 citation statements)
references
References 49 publications
11
189
2
7
Order By: Relevance
“…Mental health HCWs reported blurred roles when colleagues became clients [23]. In a study from the Netherlands, the most evident moral stressor was insufficient emotional support for patients and relatives [16]. Experiences of stress for all groups of HCWs included the inability to provide emotional support to patients when they or their relatives were anxious and stressed as well as the inability to provide a dignified death for the patient's relatives [16].…”
Section: Moral Stressors During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health HCWs reported blurred roles when colleagues became clients [23]. In a study from the Netherlands, the most evident moral stressor was insufficient emotional support for patients and relatives [16]. Experiences of stress for all groups of HCWs included the inability to provide emotional support to patients when they or their relatives were anxious and stressed as well as the inability to provide a dignified death for the patient's relatives [16].…”
Section: Moral Stressors During Covid-19mentioning
confidence: 99%
“…Moral distress is a prominent phenomenon in healthcare professions [5][6][7][8][9] that has been studied across different aspects of healthcare provision, especially in nursing [5,6,8]. While there is not a unified definition of who constitutes a healthcare worker (HCW) across studies measuring MD and/or MI, other groups that have been studied in this context include physicians [10][11][12][13][14][15][16][17][18][19][20][21], mental health workers (e.g., psychologists and psychotherapists) [3,19,20,22,23], and chaplains [15]. In general, HCWs have been conceptualized as individuals who actively engage in the protection and the improvement of the health of society [24].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that moral distress ratings have varied due to an individual's occupation (Donkers et al . 2021 ; Dryden‐Palmer et al . 2020 ; Kok et al .…”
Section: Introductionmentioning
confidence: 99%
“…During Coronavirus Disease (COVID-19) Pandemic, problems such as the increased stress, faster care, use of personal protective equipment, not allowing patients' families to visit due to their risk of infection, and many other factors make the situation more critical in addition to previous stressors (20). Moreover, working in unfamiliar environments, participating in unknown processes, workforce shortages, existing more the patients in need of the urgent care at the same time, fear of infection, new waves of the disease, deadly nature, and disease disability are challenged the nurses' decision-making between doing what is morally right and doing what is cost-effective (20,21).…”
Section: Abbaszadeh Et Al Indicated the Moderate Moral Distress Of The Nurses In Different Wardsmentioning
confidence: 99%